How much do we know about constipation after surgery for anorectal malformation? - Paul Chia-Yu Chang; Yih-Cherng Duh; Yu-Wei Fu; Yao-Jen Hsu; Chin-Hung Wei; Hsuan Huang (Pediatrics and Neonatology)
Background: To evaluate the occurrence of constipation after anorectal malformations (ARM) repair and the results of laxative treatment. Methods: Between August 2012 and July 2017, the clinical data of patients with ARMs was prospectively collected. The patients were divided into two groups, good types and poor types. Good types included rectoperineal, rectovestibular, rectourethral bulbar, and no fistula. Risk factors were defined as spinal cord anomalies, sacral ratio <0.4, or cognitive impairment. Success was defined as that laxative could be tapered. Results: Eighty-four patients were enrolled with mean age of 6.3 ± 7.8 (0.6–59.9) years. The mean age of onset of constipation was 12.8 ± 8.3 months and the mean interval was 5.9 ± 5.1 months after reconstructions. The interval was not significantly different between patients with good types and poor types. In 23 patients with severe constipation being treated for >6 months, 14 of 18 (77.8%) patients with good types were classified as success, whereas only 1 of 5 (20%) patients with poor types was (p = 0.02). In patients with good types, 9 of 9 (100%) patients with no risk factors were successful; however, only 5 out of 9 (55.6%) patients with risk factors were successful (p = 0.02). Conclusion: Constipation occurs shortly after operations. Patients with good types and no risk factors are susceptible to weaning laxatives. Key Words: anorectal malformation, bowel function, constipation, laxative, megarectosigmoid